A systematic review of the effects of team climate on software team productivity - Soomro, Arjumand Bano; Salleh, Norsaremah (2014)
The term team-work has been a significant topic in software engineering over the past 50 years. The team climate is the exchange of ideas and perceptions among team members in favor to promote the innovation in work processes. In this paper, we presented our work on a systematic review on the effect of team climate on the software productivity or performance. The summarized results from this research would be useful for achieving effectiveness in software engineering work teams.